Progression in size of an arterio-venous malformation - Shah, Abhidha (Asian J Neurosurg, 2017)
We report a case of a young girl who was admitted with history of sudden onset left hemiplegia, when she was 5 years old. Investigations revealed no vascular malformation or abnormality. On conservative treatment, she progressively improved and had residual hemiparesis. She continued to have intermittent episodes of generalized and focal convulsions. For persistent convulsions, she was investigated again with MRI and angiography after 5 years of first presentation. Investigations at this time revealed a large arteriovenous malformation in the left posterior frontal region. The arteriovenous malformation was resected by surgery. Following surgery, the episodes of convulsions reduced. Arteriovenous malformations are generally considered to be congenital lesions and their size and physical architecture generally remains constant. The presented case clearly demonstrated de novo appearance or growth of the size of the arteriovenous malformation. Such a pattern of development and growth of a arteriovenous malformation is rare and only infrequently reported.